Convergence of technologies in the conditions of the import substitution strategy as the imperative to overcome the industrial crisis in Russia - N. V. Viderker; S. R. Yunusova (Путеводитель предпринимателя, 2020)
This article discusses the issues of growing relevance for the development of new technologies in Russia in the conditions of the import substitution strategy, identified the need for convergence of communication and information in order to overcome the crisis and identified appropriate areas for the development of innovative engineering.